2011
DOI: 10.1002/syn.20917
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine effects on ventral tegmental area dopamine and GABA neuron inhibition: A physiologic role for Connexin-36 gap junctions

Abstract: Connexin-36 (Cx36) gap junctions (GJs) appear to be involved in the synchronization of GABA interneurons in many brain areas. We have previously identified a population of Cx36-connected ventral tegmental area (VTA) GABA neurons that may regulate mesolimbic dopamine (DA) neurotransmission, a system implicated in reward from both natural behaviors and drugs of abuse. The aim of this study was to determine the effect mefloquine (MFQ) has on midbrain DA and GABA neuron inhibition, and the role Cx36 GJs play in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Thus, MFQ has multiple effects that need to be considered with any interpretation regarding its effects. However, we have shown previously in midbrain slice studies that its GJ blocking effects predominate, and may be exclusively operational, after 1 hr of administration [55], which was the time delay we chose to study its effects on kindled seizures. Furthermore, in this previous study, we demonstrated that GABA inhibition to VTA dopamine neurons following MFQ treatment was markedly enhanced, nearly 5X over control or baseline conditions, suggesting that uncoupling GABA neurons from their electrotonic load increases their rate of firing and ultimately their inhibitory drive to dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, MFQ has multiple effects that need to be considered with any interpretation regarding its effects. However, we have shown previously in midbrain slice studies that its GJ blocking effects predominate, and may be exclusively operational, after 1 hr of administration [55], which was the time delay we chose to study its effects on kindled seizures. Furthermore, in this previous study, we demonstrated that GABA inhibition to VTA dopamine neurons following MFQ treatment was markedly enhanced, nearly 5X over control or baseline conditions, suggesting that uncoupling GABA neurons from their electrotonic load increases their rate of firing and ultimately their inhibitory drive to dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that MFQ blocks electrical coupling between VTA GABA neurons in adult mice [25,55] and reduces brain stimulation reward [52]. While MFQ is selective for GJs, it has other physiologically-relevant non-specific effects.…”
Section: Pharmacology Of Kindled Seizures In Wild-type Vs Connexin-36mentioning
confidence: 99%
See 1 more Smart Citation
“…All neurons classified as VTA GABA neurons in vivo were located in the VTA, and met the criteria established in previous studies for spike waveform characteristics in rats [24][25][26], and in mice [27,28]. Presumed VTA GABA neurons were characterized by short-duration (<200 µsec; measured at half-peak amplitude of the spike), initially negative-going, relatively fast-firing (10-80 Hz), non-bursting spikes.…”
Section: Characterization Of Vta Gaba Neurons In Vivomentioning
confidence: 99%
“…Substantia nigra compacta (SNc) was then identified medial to SNr. GABA neurons in the VTA were studied by visualizing GAD+ neurons in an area medial to the glowing SNr, posterior to the fasciculus retroflexus and mammillothalamic tract, and anterior to the decussation of the superior cerebellar peduncle [27,28]. Neurons in the VTA of GAD-GFP mice that did not fluoresce but exhibited a non-cation specific inward rectifying current (I h ), in combination with relatively low input resistance and regular, slow spike activity were assumed to be DA neurons [25,27,28,30,31].…”
Section: Characterization Of Vta Gaba Neurons In Vitromentioning
confidence: 99%